2017
DOI: 10.1002/14651858.cd008075.pub3
|View full text |Cite
|
Sign up to set email alerts
|

High-volume haemofiltration for sepsis in adults

Abstract: High-volume haemofiltration for sepsis in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 48 publications
0
52
0
5
Order By: Relevance
“…Whereas some studies found an improvement of hemodynamic parameters and a lower than expected mortality [23][24][25][26], the IVOIRE (high volume in intensive care) RCT failed to find a significant difference in mortality between the high-volume group (70 mL·kg -1 ·h -1 ) and the standard volume group (35 mL·kg -1 ·h -1 ), but also it could not find an improvement in secondary outcomes such as hemodynamic parameters, severity scores and length of stay [27]. This absence of beneficial effects was confirmed by 2 recent meta-analyses [28,29].…”
Section: Removing Cytokinesmentioning
confidence: 98%
“…Whereas some studies found an improvement of hemodynamic parameters and a lower than expected mortality [23][24][25][26], the IVOIRE (high volume in intensive care) RCT failed to find a significant difference in mortality between the high-volume group (70 mL·kg -1 ·h -1 ) and the standard volume group (35 mL·kg -1 ·h -1 ), but also it could not find an improvement in secondary outcomes such as hemodynamic parameters, severity scores and length of stay [27]. This absence of beneficial effects was confirmed by 2 recent meta-analyses [28,29].…”
Section: Removing Cytokinesmentioning
confidence: 98%
“…Recently, CRRT, as an effective adjuvant therapy, is proved to improve the survival of patients with severe sepsis. HVFH was an efficacious choice in removing the inflammatory mediators and improving clinical outcome in adult patients with sepsis [35]. However, no clear evidence has been emerged for the benefits of HVFH on the severe sepsis treatment in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments indicated that high-volume hemofiltration (HVHF), as a model of the CRRT techniques, improves hemodynamic recovery through removing soluble inflammatory mediators [16,17,18,19]. Moreover, HVHF is considered as an effective management to improve outcomes of patients with severe sepsis [20,21,22,23]. As it was noted previously, HVHF could maintain acid-base, azotemic, and fluid balances and also had the potential to modulate the immune system body response to sepsis [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review published in 2017 concluded: no clear evidence showed any benefit of high volume haemofiltration in critically ill patients with severe sepsis or septic shock [47]. The failure of renal replacement to improve mortality in sepsis, and the absence of cellular injury in renal failure, suggests that the decrease in glomerular filtration rate in sepsis may be a regulated trait, not a dysregulated one.…”
Section: Organ Failurementioning
confidence: 99%